Ebi3 promotes T- and B-cell division and differentiation via STAT3. (March 2019) - Ma, Ning; Fang, Ying; Xu, Ruonan; Zhai, Bing; Hou, Chunmei; Wang, Xiaoqian; Jiang, Zhenyu; Wang, Liang; Liu, Qilin; Han, Gencheng; Wang, Renxi
Highlights: Ebi3 promotes T-activation and Th1, Th17 and Treg cell differentiation. Anti-Ebi3 antibody suppresses T-cell division and differentiation. Ebi3 expresses in activated B cells and plasma cells. Ebi3 promotes B-cell division and differentiation. Ebi3 induced STAT3 signaling via gp130. Abstract: Although sharing the same subunit Ebi3, IL-27 (p28/Ebi3) and IL-35 (p35/Ebi3) have different biological functions, suggesting that Ebi3 subunit may functions as a carrier. Our data demonstrated that activated T cells and B cells effectively up-regulated Ebi3 expression. In addition, Ebi3 effectively promoted T-cell activation and the differentiation of helper T 1 (Th1), Th17, and Foxp3 + regulatory T (Treg) cells induced by Th1, Th17, and Treg polarizing condition, respectively. Naturally, Ebi3 could promote B-cell activation and the production of CD138 + plasma cells (PC) induced by LPS. Conversely, neutralizing anti-Ebi3 antibody could significantly suppress T/B-cell activation and production of Th1, Th17, Tregs, and PC induced by Th1, Th17, Treg polarizing condition, and LPS, respectively. Furthermore, we found that Ebi3 time-dependently induced STAT3 activation in CD4 + T cells and B cells. Conversely, STAT3 −/− effectively reduced Ebi3 expression and the production of Th1, Th17, Tregs, and plasma cells. Finally, we showed that gp130 but not IL-27Rα mediates Ebi3-induced STAT3 activation. These results suggest that Ebi3 promotes Th- and B-cell differentiation via gp130-STAT3 signaling pathway. Thus, autocrine Ebi3 may play an important role in the differentiation of Th and B cells and thus in infection, inflammation, and autoimmune disorders.